Effect of Particle Shape on Pipeline Damage in Liquid-Solid Two-Phase Flow. (August 2019) - Chen, Lumin; Zhao, Zhiyong; Zhang, Shijie; Sun, Yuxiang
Abstract: The shield machine is an indispensable mechanical equipment in the construction of urban rail transit. The mud shield is currently the most commonly used in urban rail transit construction. For the circulation system of the mud-water shield, the damage of the different shapes of the particles to the slurry pipeline was studied. According to the shape of clay, stone and gravel in practice, five different shapes of particle models were established for the sake of simplicity. In order to better study the characteristics of different materials, the particle model was established by discrete element software EDEM, and the mud model was established by fluid software Fluent. The fluid model is then coupled to the particle model in the discrete element. The effect of the movement of the particles in the pipe and the presence of the particles on the flow of the slurry in the pipe is analyzed. The study found that under the same volume, the shape of the particles has little effect on the fluid, but the damage to the pipeline is quite different. Among them, the lower the sphericity, the greater the collision number and energy loss between the particles and the pipeline.